2021
DOI: 10.1017/dmp.2021.164
|View full text |Cite
|
Sign up to set email alerts
|

Developing Public Health Emergency Response Leaders in Incident Management: A Scoping Review of Educational Interventions

Abstract: During emergency responses, public health leaders frequently serve in incident management roles that differ from their routine job functions. Leaders’ familiarity with incident management principles and functions can influence response outcomes. Therefore, training and exercises in incident management are often required for public health leaders. To describe existing methods of incident management training and exercises in the literature, we queried 6 English language databases and found 786 relevant articles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 670 publications
0
2
0
Order By: Relevance
“…PHE education and training had important impacts on response capacities, which had been researched in many studies [20][21][22]. However, studies have paid more attention to emergency management education and PHE training of leaders [23]. The related education and training were also important amongst healthcare workers in the analysis so they could understand the whole management, more clearly see what they could do, and understand the value of the prevention and control of PHEs.…”
Section: Discussionmentioning
confidence: 99%
“…PHE education and training had important impacts on response capacities, which had been researched in many studies [20][21][22]. However, studies have paid more attention to emergency management education and PHE training of leaders [23]. The related education and training were also important amongst healthcare workers in the analysis so they could understand the whole management, more clearly see what they could do, and understand the value of the prevention and control of PHEs.…”
Section: Discussionmentioning
confidence: 99%
“…This mainly involved experiential learning, technology assisted decision support tools, leadership, adaptability, and character. The research results indicated that these training contents enhanced the emergency management ability of leaders ( 11 ). Chiang et al ( 12 ) conducted a qualitative study to determine the factors that motivated federal public health workers to continue working on-site during emergencies.…”
Section: Related Workmentioning
confidence: 96%
“…Li et al ( 11 ) obtained information from multiple databases through literature review to cultivate the emergency management ability of leaders in PHE. This mainly involved experiential learning, technology assisted decision support tools, leadership, adaptability, and character.…”
Section: Related Workmentioning
confidence: 99%
“…However, adaptive leadership in health care and doctors’ crisis leadership have not been examined in depth beyond the doctor-patient dynamics (Anderson et al , 2015). Personal competencies, though important for crisis leadership in public health (Li et al , 2021), are not adequately examined and researchers have to refer to other sectors such as the military and aviation (Deitchman, 2013). Furthermore, competency frameworks, though useful, are mostly universal irrespective of contextual factors, individual differences and existing and future and work requirements (Bolden and Gosling, 2006).…”
Section: Introductionmentioning
confidence: 99%